The Centrosomal Linker and Microtubules Provide Dual Levels of Spatial Coordination of Centrosomes - Panic, Marko; Hata, Shoji; Neuner, Annett; Schiebel, Elmar (PLOS Genetics, 2015)
Author Summary During most of interphase, the two centrosomes of a cell are kept together by a proteinaceous linker, called the centrosomal linker. It is clear that the linker has to be dissolved by Nek2 kinase and other mechanisms before mitosis in order to assemble a functional bipolar mitotic spindle. Yet the relevance of the centrosome linker for cell function during interphase is not understood. Here we describe for the first time the analysis of a knockout (KO) cell line that lacks an essential component of the centrosome linker, C-Nap1. We observed that centrosomes in these cells are devoid of linker proteins and Nek2 kinase whereas other centrosomal proteins localize to centrosomes as in wild type cells. On average the centrosome distance is moderately increased in C-Nap1 KO cells from 1 to 2.5 μm. We further show that the centrosomal linker is only one element that positions centrosomes close to each other in interphase cells. In linker deficient cells, microtubules spatially organize centrosomes. This resolves a long discussed issue on the role of microtubules in centrosome cohesion. Moreover, we observed that linker deficient cells mis-organize the Golgi. Furthermore, migration of C-Nap1 KO cells was slower than their wild type RPE1 counterparts.